Answer:
1.5 bananas.
Step-by-step explanation:
1.5 x 2 = 3
Answer:
1.5
Step-by-step explanation:
3 divided by 2 is 1.5
The following shows the floorplan for a room that is being added on to your house. If the scale factor is 2.5” = 3 ft, what is the area of the room in the real world?
Answer:
9 ft
Step-by-step explanation:
you multiply side a by side b
so 3x3 = 9 ft
Radius of cone 15cm in height and 16cm in length
Final answer:
The curved surface area of a cone with a radius of 15 cm and a slant height of 16 cm is 753.982 cm², calculated using the formula A = πrl.
Explanation:
The question asks for the curved surface area of a cone with a given radius and slant height. To find the curved surface area of a cone, we use the formula:
A = πrl
where A is the area, π is pi (approximately 3.14159), r is the radius, and l is the slant height of the cone.
Here, the radius (r) is 15 cm and the slant height (l) is 16 cm. Substituting these values into the formula, we get:
A = π × 15 cm × 16 cm
A = 3.14159 × 15 cm × 16 cm
A = 753.982 cm²
Therefore, the curved surface area of the cone is 753.982 cm².
If Ed can paint the bedroom by himself in 3 hours, and his friend , Jake, works at the same pace as Ed does , how long will it take to paint the room if the boys work together?(shoe work)
Answer:
1.5
Step-by-step explanation:
1 person = 3 hours
2 people = 1.5 hours
Answer:
1 hour and 30 minutes
Step-by-step explanation:
Each one of them needs 3 hours to paint the bedroom,but now they are 2 people who work at the same place so together,they only need half of the time.
Look at the following numbers:
-4, -1,0,4
Which pair of numbers has a sum of 0?
Answer:
-4 + 4
Step-by-step explanation:
because when you add a negative number with a positive number the sum will always equal 0
I am joyus to assist :)
Answer:
-4+4
Step-by-step explanation:
what 1/8 of 12 in simplest form
Answer:
1½
Step-by-step explanation:
[tex] \frac{1}{8}(12) = \frac{12}{8} = 1 \frac{4}{8} = 1 \frac{1}{2} [/tex]
I am joyous to assist you anytime.
Complete the factorization of 4x2 – 9.
4x2-9= ( x-
x+ )
Answer:
1.) 2
2.) 3
3.) 2
4.) 3
Step-by-step explanation:
Help with number 1 plz
Yes, it will! It will be the same because of the Commutative property. Hope this gives you your whole answer!
Suppose the function h(t) gives the heart rate of a runner at various points in time, t, during a 10 mile run. Select an appropriate domain for this function. Assume that the runner completed the 10 mile run in 112 minutes.
Write the domain of this function using interval notation.
The domain of the heart rate function h(t) for a runner who completed a 10-mile run in 112 minutes is [0, 112] in interval notation.
Explanation:In this scenario, the domain of the function h(t) is the time duration during which the runner is running. Thus, since the runner completed the 10-mile run in 112 minutes, the domain is from 0 (the start of the run) to 112 (the end of the run). We represent this in interval notation as [0, 112]. The square brackets indicate that the endpoints are included in the domain. So, the domain of the function h(t) in this context is [0, 112].
Learn more about Domain of a function here:https://brainly.com/question/28599653
#SPJ3
12 hundredths = how many tenths and hundredths
At the grand opening, every 8th customer received a free coffee mug, and every 12th customer received a free baseball cap. How many of the first 100 customers received both a mug and a cap?
8 people received a Baseball Cap
12 people received a Coffee Mug
Hope this helped!
10. Find the sum -18 + (-36).
Answer: -54
All you need to do is add the two together
Answer:
Step-by-step explanation:
-18 + (-36) = -18-36 = -54
how to get 654 divided by 3 with partial quotients
Answer:
218 every part
Step-by-step explanation:
654/3 = 218
what is 1 plus 5.00
A. 5.01
B.1
C. 12345678
D. 501
Answer:
Step-by-step explanation:
501
Simplify the square root of 5 times the cube root of 5.
five to the five sixths power
five to the one sixth power
five to the two thirds power
five to the seven sixths power
Answer:
Option 3 - five to the two thirds power
Step-by-step explanation:
Given : Expression 'the square root of 5 times the cube root of 5'.
To find : Simplify the expression ?
Solution :
Writing expression in numeric form,
The cube root of 5 means [tex]\sqrt[3]{5}[/tex]
The square root of 5 times the cube root of 5 means [tex]\sqrt{5\sqrt[3]{5}}[/tex]
Now, simplify the expression
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{5\times (5)^{\frac{1}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{(5)^{1+\frac{1}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=\sqrt{(5)^{\frac{4}{3}}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=((5)^{\frac{4}{3}})^{\frac{1}{2}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=(5)^{\frac{4}{3}\times \frac{1}{2}}[/tex]
[tex]\sqrt{5\sqrt[3]{5}}=(5)^{\frac{2}{3}}[/tex]
The expression is five to the two thirds power.
Therefore, Option 3 is correct.
The correct option is d. To simplify [tex]\(\sqrt{5} \cdot \sqrt[3]{5}\)[/tex], we get [tex]\(5^{5/6}\)[/tex]. Therefore, the correct answer is five to the seven sixths power.
To simplify [tex]\( \sqrt{5} \times \sqrt[3]{5} \)[/tex], we combine the radicals:
[tex]\[ \sqrt{5} \times \sqrt[3]{5} = 5^{1/2} \times 5^{1/3} \][/tex]
Using the property of exponents [tex]\( a^m \times a^n = a^{m+n} \)[/tex]:
[tex]\[ 5^{1/2} \times 5^{1/3} = 5^{1/2 + 1/3} \][/tex]
Now, find a common denominator for the exponents:
[tex]\[ \frac{1}{2} + \frac{1}{3} = \frac{3}{6} + \frac{2}{6} = \frac{5}{6} \][/tex]
Therefore,
[tex]\[ 5^{1/2} \times 5^{1/3} = 5^{5/6} \][/tex]
So, the simplified expression is [tex]\( {5^{5/6}} \).[/tex]
This corresponds to option (d) in your choices: five to the seven sixths power.
The complete question is- Simplify the square root of 5 times the cube root of 5.
a. five to the five sixths power
b. five to the one sixth power
c. five to the two thirds power
d. five to the seven sixths power
The first two steps in the derivation of the quadratic formula by completing the square are shown below.
Which answer choice shows the correct next step?
Step 1: ax^2+ bx+c = 0
Step 2: ax^2 + bx=-c
Answer:
The correct next step is the answer choice
[tex]x^{2} +\frac{b}{a}x=-\frac{c}{a}[/tex]
Step-by-step explanation:
we have the quadratic equation in standard form
[tex]ax^{2}+bx+c=0[/tex]
The steps in the derivation of the quadratic formula by completing the square are
step 1
[tex]ax^{2}+bx+c=0[/tex] ----> given equation
step 2
Move the constant term over to the right-hand side
[tex]ax^{2}+bx=-c[/tex]
step 3
The leading term is multiplied by a
so
Divide by a both sides
[tex]x^{2} +\frac{b}{a}x=-\frac{c}{a}[/tex]
step 4
Multiply the linear term by 1/2
[tex]\frac{b}{a}(\frac{1}{2})=+\frac{b}{2a}[/tex]
step 5
square this derived value
[tex]+\frac{b^2}{4a^2}[/tex]
step 6
Add this squared value to either side of the equation
[tex]x^{2} +\frac{b}{a}x+\frac{b^2}{4a^2}=-\frac{c}{a}+\frac{b^2}{4a^2}[/tex]
step 7
convert to the common denominator, and combine on the right-hand side
[tex]x^{2} +\frac{b}{a}x+\frac{b^2}{4a^2}=\frac{b^2-4ac}{4a^2}[/tex]
step 8
convert the left-hand side to completed-square form
[tex](x+\frac{b}{2a})^{2}=\frac{b^2-4ac}{4a^2}[/tex]
step 9
take the square roots of either side
[tex](x+\frac{b}{2a})=(+/-)\sqrt{\frac{b^2-4ac}{4a^2}} \\\\(x+\frac{b}{2a})=(+/-)\frac{\sqrt{b^2-4ac}}{2a}[/tex]
step 10
solving for the variable
[tex]x=-\frac{b}{2a}(+/-)\frac{\sqrt{b^2-4ac}}{2a}\\\\x=\frac{-b(+/-)\sqrt{b^2-4ac}}{2a}[/tex]
Answer:
C on edge
Step-by-step explanation:
1/8 is called a terminating decimal
Explain
Answer:
Step-by-step explanation:
Maybe if we defined a non terminating fraction first, a terminating one would make more sense to you.
non terminating means that it goes on forever.
1/3 = 0.3333333333333333333333333333333....333333333333333333...333
I/3 never really ends.
1/8 on the other hand had
1/8 = 0.125 as a value and that's all there is. We're done.
So a terminating decimal ends.
The axis of symmetry for a function in the form f(x) = x2 + 4x − 5 is x = −2. What are the coordinates of the vertex of the graph?
Answer:
The coordinates of the vertex of the graph are (-2, -9).
Step-by-step explanation:
The quadratic function is described by the standard equation The graph of a quadratic function is called a parabola.
We have the quadratic function
We identify the coefficients a, b, and c. For this equation,
The axis of symmetry is , i.e., Thus, the statement in the question for the symmetry axis x = -2 is correct.
The vertex (or turning point) is where or
The parabola opens upward because a > 0, resulting in a vertex that is a minimum.
Finding the minimum value is as follows:
Therefore, the coordinates of the vertex of the graph are (h, k), i.e.,
Other components:
The y-intercept of the quadratic function f(x) = x² + 4x - 5 is (0, c), i.e., the point
The factorization of f (x) = x² + 4x - 5 becomes f(x) = (x + 5)(x - 1). Then we get the x-intercepts at
Learn more
Which is the graph of f(x) = (x - 1)(x + 4) brainly.com/question/2334270
Finding the y-intercept of the quadratic function f(x) = (x – 6)(x – 2) brainly.com/question/1332667
The midpoint brainly.com/question/3269852
Keywords: the axis of symmetry, for a function, f(x) = x² + 4x − 5, x = −2, which is the graph of f(x) = (x - 1)(x + 4), what, the coordinates of the vertex of the graph, the x-intercept, quadratic function, a standard equation, the y-intercept, parabola, upward, the minimum value
Answer:
the vertex of the graph is (-2, -9)
Step-by-step explanation:
The given function is:
[tex]f(x)=x^2+4x-5[/tex]
Given x = -2 is the axis of symmetry and because we know that the vertex of the graph lies on its axis of symmetry
=> coordinate of vertex is (-2, y)
When x= -2 we have
[tex]f(-2) =(-2)^2+4(-2)-5\\<=> y=4-8-5\\<=> y=-9[/tex]
So the vertex of the graph is (-2,-9)
The local pharmacy has a coupon for two-in-one shampoo and conditioner. The original cost of one bottle is $6.99, and the coupon is for $1.75
off. How much does one bottle cost when the coupon is applied?
$6.99
$5.24
$5.00
$1.75
Answer:
5.24
Step-by-step explanation:
6.99-1.75 is 5.24.
Answer:
$5.24
Step-by-step explanation:
[tex]\begin{array}{rcr}\text{Original cost} & = & 6.99\\\text{Less coupon} & = & -1.75\\\text{Net cost} & = & \mathbf{5.24}\\\end{array}[/tex]
Simplify the following expression. 2^2 • 2^3
The simplification of the expressions give above would be = 32
How to simplify the given expression?To simplify the given expression the following steps needs to be taken as follows:
2²× 2³
Where;
2² = 2×2
2³ = 2×2×2
The simplification = 2×2×2×2×2= 32
Learn more about multiplication here:
https://brainly.com/question/29793687
#SPJ2
Evaluate B^2for B=9.
Answer:
81
Step-by-step explanation:
since b is 9
do 9x9 which is 81
28.9-32.5
i will be fine i just forget the steps
Answer:
-3.6
Step-by-step explanation:
Since 32.5 is greater than 28.9, you just subtract 32.5 from 28.9 then add an equal sign. 32.5-28.9=3.6. With the negative, it would be -3.6
The value obtained by making the subtraction operation is -3.6
Subtracting ValuesTo perform the subtraction operation, the right hand side value is taken away from left hand side value .
Here , we have;
28.9 - 32.5 = -3.6We obtained a negative value because the right hand value is greater than the left hand value.
Learn more on numbers ::https://brainly.com/question/24997908
#SPJ3
Solve for x.
0 = 7x² + x + 5
a x=−1±i139‾‾‾‾√14
b x=−1±i105‾‾‾‾√14
c x=−1±i34‾‾‾√14
d x=−1±i120‾‾‾‾√14
Answer:
[tex]a \: \: x = \frac{ -1 ± i\sqrt{139}}{14} [/tex]
Explanation:
Since this is unfactorable, use the Quadratic Formula:
[tex]x = -b ± \frac{ \sqrt{ {b}^{2} - 4ac}}{2a} [/tex]
Now, take the information and input it:
[tex] -1 ± \frac{ \sqrt{1 - 4(7)(5)}}{2(7)} \\ \\ -1 ± \frac{ \sqrt{ -139}}{ 14} = \frac{-1 ± i\sqrt{139}}{14} [/tex]
I am joyous to assist you anytime.
Fill in the blank to make the following statement true: 1,426 centigrams = _____ kilograms
A : 0.01426
B : 14.26
C : 1.426
D : 0.1426
Answer: A. 0.01426
Step-by-step explanation:
divide the mass value by 100000
Answer:
A. 0.01426
Step-by-step explanation:
divide by 10000
8x-4y=-12;x=-3,-1,1 do not know how to the assignment
Answer:
y= -3,1,5
Step-by-step explanation:
actually the question is what are the values of y when x = -3,-1,1
Answer: -1=-1 ,1=1
You just need to plug it in to the graph.
Jada says: “If you multiply a number by 0.001, the decimal point of the number moves three places to the left.” Do you agree with her statement? Explain your reasoning.
pls help
Step-by-step explanation:
Yes, I agree with her. If you multiply a number by .001 youll move the decimal point to the left 3 times. For example let's say 480. multiplied by .001. it will then become .480 or .48
Yes I agree I just did this in class
Given that y=3(4x - 3)+5, find the value of x when y=-2.
Answer:
x=-2
Step-by-step explanation:
Distribute the 3 with the parenthesis to make the new equation -2=12x-9+5.
Combine like terms. -2=12x-4.
Move -4 to other side. -6=12x.
Divide by -6. x=-2
For which equation would x = 1 not be a solution?
x/1 = 1
x/2 = 2/4
x/3 = 3
x/4 = 1/4
Answer:
[tex] \frac{x}{3} = 3[/tex]
Step-by-step explanation:
[tex] \frac{1}{3} ≠ 3; \: \frac{9}{3} = 3[/tex]
I am joyous to assist you anytime.
Final answer:
The equation for which x = 1 is not a solution is x/3 = 3, as substituting x with 1 gives 1/3, which is not equal to 3.
Explanation:
To determine which equation x = 1 would not be a solution for, we need to substitute x with 1 in each equation and see if it holds true:
x/1 = 1: Substituting x with 1 gives us 1/1 = 1, which is true. Therefore, x = 1 is a solution.
x/2 = 2/4: Substituting x with 1 gives us 1/2 = 2/4, which simplifies to 1/2 = 1/2, also true. Hence, x = 1 is a solution.
x/3 = 3: Substituting x with 1 gives us 1/3 = 3, which is false, because 1/3 is not equal to 3. Therefore, x = 1 is not a solution here.
x/4 = 1/4: Substituting x with 1 gives us 1/4 = 1/4, which is true. Thus, x = 1 is a solution.
The equation for which x = 1 is not a solution is x/3 = 3.
20 points if you answer right !!!!!HELP PLEASE
An experiment was conducted to test the following hypothesis it rains more in California then it doesn’t Arizona which of the following would show confirmation bias A.experiment suppose the hypothesis B.The scientist ignores Arizona desert because she doesn’t think it rains thereC.Experiment focuses equally on each states rainfall D. experiment prove a hypothesis to be true
Answer:
B
Step-by-step explanation:
When Experimenting scientist must include every part of the experiment and not leave out details.
Answer:b
Step-by-step explanation:
How do I do ( +7 ) - ( -2 ) = ?
Answer:
=9
Step-by-step explanation:
7−(−2)
=7−(−2)
=7+2
=9
What sequence of events explains why Anderson did not make any money from her patent?
Anderson was unable to capitalize on her invention, and other companies were able to profit from her invention without paying her.
The sequence of events that explains why Anderson did not make any money from her patent is as follows:
Anderson invented the windshield wiper in 1903.She patented her invention in 1905.She tried to sell her patent to a Canadian company, but they refused to buy it.She tried to sell her patent to other companies, but none of them were interested.Anderson did not have enough money to market and manufacture her invention herself.Other companies began to make and sell windshield wipers without her permission.Anderson could not afford to sue the companies for patent infringement.Anderson's patent expired in 1920.Anderson never made any money from her invention.The image of Mary Anderson and the First Windshield Wipers confirms this sequence of events. The image shows Anderson with a model of her windshield wiper invention. The text below the image states that Anderson "failed to sell her patent to any manufacturer" and that "her patent expired in 1920 without her making any money from her invention."
In addition to the information in the image, we can also infer that Anderson did not make any money from her patent because she did not have the business acumen or resources to bring her invention to market. She was a single woman with no business experience. She also did not have the financial resources to manufacture and market her invention on her own.